Theories of Money Supply: The Relationship of Money Supply in a Period of Time T-1 and Inflation in Period T- Empirical Evidence from Albania - Koti, Sorina; Tomi Bixho (European Journal of Multidisciplinary Studies, 2016)
The aim of this paper is to present different approaches and theories, which are linked with money and inflation. Many studies are made to provide a high relationship of money and inflation. The changes in money supply always have affected the macroeconomic indicators such as inflation, unemployment, economic growth, trades and have let the governments to conduct the necessary fiscal and monetary policies, in order to react in an efficient way to reduce uncertainty and to build a sustainable economy. The paper analyses the theoretical links of money supply with unemployment, trade and exchange rate, taxes and wages. The regression analysis is conducted based on the theories of money. The analysis and the empirical results for Albania showed that money supply has strong relationship with economic growth, interest rate and inflation, but money supply has a negative sign toward inflation, by arguing that the case of Albania is specific, because of lack of money supply from banking system and money in circulation outside banks. From the results, we found that all money supplied by the financial system is fully absorbed by the private sector and individuals, without causing an increase on the inflation level. This may be argued from the financial crisis that affected Albania and the reduction of production, consumption, unemployment and delayed payments from the government toward business sector. Furthermore, there are suggested monetary policies for increasing the supply of money, and fiscal policies for increasing the demand for goods and services. The supply increases by the demand side, which need to be stimulated by production sector through fiscal policies and government development programs